Experimental Study and Design of a Submerged Membrane Distillation Bioreactor - Phattaranawik, J.; Fane, A. G.; Pasquier, A. C. S.; Bing, W.; Wong, F. S. (Chemical engineering & technology, 2009)
A hybrid process incorporating membrane distillation in a submerged membrane bioreactor operated at elevated temperature is developed and experimentally demonstrated in this article. Since organic particles are rejected by an ‘evaporation’ mechanism, the retention time of non‐volatile soluble and small organics in the submerged membrane distillation bioreactor (MDBR) is independent of the hydraulic retention time (mainly water and volatiles). A high permeate quality can be obtained in the one‐step compact process. The submerged MD modules were designed for both flat‐sheet membranes and tubular membrane configurations. The process performance was preliminarily evaluated by the permeate flux stabilities. The module configuration design and air sparging used in the MDBR process were tested. Flux declines were observed for the thin flat‐sheet hydrophobic membranes. Tubular membrane modules provided more stable permeate fluxes probably due to the turbulent condition generated from air sparging injected inside the tubular membrane bundles. The experiments with the submerged tubular MD module gave stable fluxes of approximately 5 L/m2 h over 2 weeks at a bioreactor temperature of 56 °C. The total organic carbon in the permeate was consistently lower than 0.7 mg/L for all experiments. A submerged membrane distillation bioreactor is experimentally demonstrated for wastewater reuse to produce high quality permeate in a single‐step within a compact process. Subject to the availability of waste heat/solar thermal energy and a cooling system to exchange heat with a cooler natural resource, the MDBR may offer a low primary energy process with a very high permeate quality and a stable flux, at a practical value in a small foot print configuration.